Deformation monitoring of rock slope with weak bedding structural plane subject to tunnel excavation - Song, Danqing; Chen, Jundong; Cai, Jianhua (Arabian journal of geosciences, 2018)
The deformation characteristics of rock slopes with weak structural plane are governed by the mechanical properties and geometrical distribution of the structural plane. In particular, the weak structural planes can be excavated and disturbed in the tunnel excavation process, which makes the deformation characteristics complex. Long-term monitoring using a multi-point displacement meter was used to analyse the deformation characteristics of a rock slope with weak bedding structural planes under tunnel excavation. The monitoring results show that the displacement increases with increasing excavation time and tends to eventually stabilize in the tunnel excavation process with three fast movements. The deformation is mainly within the depth of 0–10 m from the slope surface. The excavation blasting affects the slope deformation above structural plane I, and there is no obvious correlation between rainfall and the slope deformation. The excavation distance also affects the slope deformation: first, the slope deformation has a sudden increase when the excavation face arrives at a certain section; then, it further increases when the excavation face continues to increase; and finally, the deformation decreases and tends to gradually stabilize when the excavation face is far away from the section. Moreover, the weak structural plane has a great impact on the slope deformation, particularly at structural plane I. The failure mode of the slope under an external load is also discussed: the sliding body first slides along weak structural plane I and subsequently slides along structural plane II when the external load further increases.